Penggunaan Campur Kode Pada Novel Chemistry Cinta di Wakatobi Karya Dedi Oedji (Kajian Sosiolinguistik) - Arin Faridatul Azma (Jurusan Pendidikan Bahasa & Sastra Indonesia, Universitas Negeri Gorontalo, 2021)
This research analyzes the existence of mixed codes in a novel Chemistry Cinta di Wakatobi (CCW) by Dedi Oedji. This research aims to describe: 1) The use of code-mixed forms in the novel CCW by Dedi Oedji. (2) Know the function of the code-mixing in the novel CCW by Dedi Oedji. This research uses a qualitative method that is descriptive analysis. In this study using data in the form of dialogue between characters. Research data conducted sourced from novel Chemistry Cinta di Wakatobi by Dedi Oedji. As for the data collection techniques in this study by refer to the method of note and note method, because the data source is in the form of text. Based on the results of the study found the form of mixed code contained in the novel Chemistry Cinta di Wakatobi by Dedi Oedji. As for the function of mixed code that causes the occurrence of mixed code in the novel Chemistry Cinta di Wakatobi by Dedi Oedji among others: 1) Easing convey meaning, 2) Demonstrate familiarity, 3) The need for vocabulary, 4) Talking about a particular topic.